Triaryl pyran onium salt or triaryl thiapyranium salt for photocatalytic degradation of polyurethane plastic as well as preparation method and application of triaryl pyran onium salt or triaryl thiapyranium salt
By developing triaryl arylonium salt photocatalysts with a wider redox potential range and higher chemical stability, the problem of existing photocatalysts being less efficient when degrading polyurethane plastics is solved, and efficient and economical polyurethane degradation effect is achieved, with wide application prospects.
Patent Information
- Application Number
- CN202411864085.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing photocatalysts are less efficient when degrading polyurethane plastics, and the chemical recycling of commercial plastics is challenging.
A triarylionium salt was developed with a wider redox potential range, increased molar absorption in the visible spectrum, improved quantum yield, longer excited state lifetime and higher chemical stability. By regulating the structure of the photocatalyst, the redox potential range is widened, and under the irradiation of green energy light, combined with the synergistic action of acid catalyst and oxygen, the efficient degradation of polyurethane model molecules is achieved.
It improves the efficiency and degradation rate of photocatalytic degradation of polyurethane materials, has simple process and convenient operation, reduces production costs, and has broad application prospects in pollution-free treatment and recycling of plastic pollutants.
Smart Images

Figure CN119684245A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photocatalysis and plastic degradation, and in particular to a triaryl onium salt and a preparation method and application thereof. Background Art
[0002] Photocatalysis is an environmentally friendly technology that uses solar energy as a reaction driving energy, and it has an increasingly important application prospect in the field of energy and environment. In recent years, plastics such as polyurethane have become widely used products around the world due to their light weight, humanized design, chemical resistance, good thermal stability and excellent electrical insulation properties. At present, most of the huge amount of plastic waste produced and retained by humans is accumulated in landfills or natural environments. Existing methods for treating waste plastic materials include thermal degradation, catalytic degradation, mechanical degradation, chemical degradation, ozone oxidation degradation and photo-oxidative degradation. These methods have various disadvantages, some of which produce pollutants, some consume a lot of energy, and some waste resources. However, photocatalytic degradation uses abundant renewable solar energy, so photocatalytic degradation of polymers is energy-saving and inexpensive.
[0003] Commercial plastics currently in large-scale use are mainly based on performance and durability rather than degradability and recyclability. Therefore, chemical recycling of plastics is very challenging. It is worth noting that polyurethane plastics, due to the breakable carbon-carbon bonds in their polymer structure, provide the possibility of polymer depolymerization, thus showing broad research and development prospects.
[0004] Organic photocatalysts have a wider redox potential range, higher molar absorptivity and quantum yield in the visible spectrum, longer excited state lifetime and higher chemical stability, so organic photocatalysts have become the mainstream photocatalysts. However, the efficiency of organic photocatalysts is still low when degrading polyurethane. Summary of the invention
[0005] The invention provides a triaryl onium salt and a preparation method and application thereof. The triaryl onium salt of the invention has a wider redox potential range, an increase in molar absorptivity in a visible spectrum, an improvement in quantum yield, a longer excited state lifetime and a higher chemical stability.
[0006] The present invention provides a triaryl onium salt having a structure shown in Formula I:
[0007]
[0008] X is O or S, Y is BF4, PF6, SO4, ClO4, F, Cl, Br or I, wherein R 3 ~R 6Independently include one or more of hydrogen atoms, hydroxyl groups, nitro groups, cyano groups, isocyano groups, isocyanate groups, boronate groups, sulfone groups, halogen groups, alkyl groups, substituted alkyl groups, alkoxy groups, substituted alkoxy groups, phenoxy groups, aryl groups, substituted aryl groups, heteroaryl groups, acyl groups and ester groups.
[0009] Preferably, the number of carbon atoms of the alkyl, substituted alkyl, alkoxy, substituted alkoxy, acyl or ester group is independently 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15;
[0010] The number of carbon atoms of the substituted aryl and heteroaryl groups is independently 6, 7, 8, 9, 10 or 11.
[0011] Preferably, the triaryl onium salt has a structure shown in any one of PS1 to PS 9:
[0012]
[0013] The present invention also provides a method for preparing the triaryl onium salt described in the above technical solution, comprising the following steps:
[0014] The compound represented by formula II, the compound represented by formula III, an organic solvent and a first acid are mixed and subjected to a condensation cyclization reaction to obtain a triaryl onium salt in which X is O; the first acid comprises boron trifluoride etherate, hexafluorophosphoric acid, sulfuric acid, perchloric acid, hydrofluoric acid, hydrofluoric acid, hydrobromic acid or hydrobromic acid;
[0015]
[0016] The molar ratio of the compound represented by the structure of formula II to the compound represented by the structure of formula III is ≤0.5;
[0017] The triaryl onium salt wherein X is O, a solvent and a sulfide are mixed to carry out a substitution reaction, and then mixed with a second acid to acidify and form a salt, thereby obtaining a triaryl onium salt wherein X is S;
[0018] The second acid includes tetrafluoroboric acid, hexafluorophosphoric acid, sulfuric acid, perchloric acid, hydrofluoric acid, hydrofluoric acid, hydrobromic acid or hydrobromic acid.
[0019] Preferably, the molar ratio of the compound of the structure represented by Formula II to the first acid is 1:2-6.
[0020] Preferably, the molar ratio of the compound of the structure represented by formula II to the compound of the structure represented by formula III is 1:2 to 2.4.
[0021] Preferably, the molar ratio of the triaryl onium salt wherein X is O to the sulfide is 1:3-6.
[0022] Preferably, the molar ratio of the triaryl onium salt wherein X is O to the second acid is 1:30-40.
[0023] The present invention also provides the use of the triaryl onium salt described in the above technical solution or the triaryl onium salt prepared by the preparation method described in the above technical solution in photocatalytic degradation of polyurethane materials.
[0024] Preferably, the photocatalytic degradation of polyurethane material comprises the following steps:
[0025] The triaryl onium salt described in the above technical solution or the triaryl onium salt prepared by the preparation method described in the above technical solution, the polyurethane material, the alcohol compound, the acidic co-catalyst and the organic solvent are mixed and then photocatalytically degraded in an oxygen atmosphere.
[0026] The present invention broadens the redox potential range of the triaryl onium salt by regulating the structure of the photocatalyst (changing the substituents on the benzene ring), increases the molar absorptivity in the visible spectrum, and improves the quantum yield, excited state lifetime and chemical stability.
[0027] The application of the present invention uses green energy light as an energy source, adds an acidic catalyst, and utilizes the synergistic catalytic effect between triaryl onium salt photocatalyst and oxygen to achieve the degradation of polyurethane model molecules. In this method, after the photocatalyst absorbs visible light and is excited, the polyurethane material containing MDI structure (polyurethane materials containing TDI or HDI and other types of structures cannot be applied to this method) can be oxidized into free radical cations, thereby generating benzylic carbon free radicals, and under the action of superoxide anion free radicals, the CH bond is activated, and finally CC is cracked and degraded. This method has the advantages of simple process, convenient operation, high processing efficiency and degradation efficiency, and has broad application prospects in the pollution-free treatment and recycling of plastic pollutants.
[0028] The triaryl onium salt organic photocatalyst raw material of the present invention is easy to obtain commercially and is low in price, and can effectively reduce production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The present invention provides a synthesis route for the triarylpyrylium salt photocatalyst;
[0030] Figure 2 This is the H NMR spectrum of the triarylpyrylium salt photocatalyst PS1;
[0031] Figure 3 This is a diagram of the solution clarity before and after the blue light irradiation reaction in Application Example 1. DETAILED DESCRIPTION
[0032] The present invention provides a triaryl onium salt having a structure shown in Formula I:
[0033]
[0034] X is O or S, Y is BF4, PF6, SO4, ClO4, F, Cl, Br or I, wherein R 3 ~R 6 Independently include one or more of hydrogen atoms, hydroxyl groups, nitro groups, cyano groups, isocyano groups, isocyanate groups, boronate groups, sulfone groups, halogen groups, alkyl groups, substituted alkyl groups, alkoxy groups, substituted alkoxy groups, phenoxy groups, aryl groups, substituted aryl groups, heteroaryl groups, acyl groups and ester groups.
[0035] In the present invention, the number of carbon atoms of the alkyl group, substituted alkyl group, alkoxy group, substituted alkoxy group, acyl group or ester group is preferably 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15 independently.
[0036] In the present invention, the carbon number of the substituted aryl and heteroaryl groups is preferably 6, 7, 8, 9, 10 or 11 independently.
[0037] In the present invention, the triaryl onium salt has a structure shown in any one of PS1 to PS 9:
[0038]
[0039]
[0040] The present invention also provides a method for preparing the triaryl onium salt described in the above technical solution, comprising the following steps:
[0041] The compound represented by formula II, the compound represented by formula III, an organic solvent and a first acid are mixed and subjected to a condensation cyclization reaction to obtain a triaryl onium salt in which X is O; the first acid comprises boron trifluoride etherate, hexafluorophosphoric acid, sulfuric acid, perchloric acid, hydrofluoric acid, hydrofluoric acid, hydrobromic acid or hydrobromic acid;
[0042]
[0043] The molar ratio of the compound represented by the structure of formula II to the compound represented by the structure of formula III is ≤0.5;
[0044] The triaryl onium salt wherein X is O, a solvent and a sulfide are mixed to carry out a substitution reaction, and then mixed with a second acid to acidify and form a salt, thereby obtaining a triaryl onium salt wherein X is S;
[0045] The second acid includes tetrafluoroboric acid, hexafluorophosphoric acid, sulfuric acid, perchloric acid, hydrofluoric acid, hydrofluoric acid, hydrobromic acid or hydrobromic acid.
[0046] The present invention mixes a compound with a structure shown in formula II, a compound with a structure shown in formula III, an organic solvent and a first acid, and then performs a condensation cyclization reaction to obtain a triaryl onium salt in which X is O.
[0047] In the present invention, the mixing preferably includes mixing the compound having a structure represented by Formula II, the compound having a structure represented by Formula III and an organic solvent in a protective atmosphere and then mixing with the first acid.
[0048] In the present invention, the molar ratio of the compound of the structure represented by formula II to the first acid is preferably 1:2-6. In a specific embodiment of the present invention, the molar ratio of the compound of the structure represented by formula II to the first acid can be 1:2, 1:2.4, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5 or 1:6; the first acid includes boron trifluoride etherate, hexafluorophosphoric acid, sulfuric acid, perchloric acid, hydrofluoric acid, hydrofluoric acid, hydrobromic acid or hydrobromic acid.
[0049] In the present invention, the molar ratio of the compound of the structure represented by formula II to the compound of the structure represented by formula III is preferably 1:2 to 2.4. In a specific embodiment of the present invention, the molar ratio of the compound of the structure represented by formula II to the compound of the structure represented by formula III can be 1:2, 1:2.1, 1:2.2, 1:2.3 or 1:2.4.
[0050] In the present invention, the ratio of the compound of the structure shown in formula II to the organic solvent is preferably 0.001 to 0.005 mol:4 mL. In a specific embodiment of the present invention, the ratio of the compound of the structure shown in formula II to the organic solvent can be 0.001 mol:4 mL, 0.002 mol:4 mL, 0.003 mol:4 mL, 0.004 mol:4 mL or 0.005 mol:4 mL; the organic solvent preferably includes one or more of toluene, o-xylene, chlorobenzene and fluorobenzene. When the organic solvent is toluene and o-xylene, the volume ratio of toluene to o-xylene is preferably 1:1.
[0051] In the present invention, the temperature of the condensation cyclization reaction is preferably 70-200°C, and the time is preferably 1-24h; in a specific embodiment of the present invention, the temperature of the condensation cyclization reaction can be 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, or 200°C, and the time of the condensation cyclization reaction can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h or 24h.
[0052] In the present invention, after the condensation cyclization reaction, the present invention preferably further comprises: mixing the product obtained from the condensation cyclization reaction with diethyl ether to precipitate the triaryl pyrylium salt, and after solid-liquid separation, subjecting the obtained crude triaryl pyrylium salt to column chromatography to obtain the triaryl pyrylium salt.
[0053] After obtaining the triaryl onium salt in which X is O, the present invention mixes the triaryl onium salt in which X is O, a solvent and a sulfide for a substitution reaction, and then mixes the mixture with a second acid for acidification to form a salt, thereby obtaining the triaryl onium salt in which X is S.
[0054] In the present invention, the molar ratio of the triaryl onium salt wherein X is O to the sulfide is preferably 1:3-6. In a specific embodiment of the present invention, the molar ratio of the triaryl onium salt wherein X is O to the sulfide may be 1:3, 1:3.6, 1:4, 1:4.5, 1:5, 1:5.5 or 1:6; the sulfide preferably includes one or more of hydrogen sulfide, lithium sulfide, sodium sulfide, potassium sulfide, cesium sulfide, magnesium sulfide and calcium sulfide.
[0055] In the present invention, the temperature of the substitution reaction is preferably room temperature. The present invention has no particular limitation on the time of the substitution reaction, as long as the reaction is complete.
[0056] In the present invention, the molar ratio of the triaryl onium salt wherein X is O to the second acid is preferably 1:30-40. In a specific embodiment of the present invention, the molar ratio of the triaryl onium salt wherein X is O to the second acid may be 1:30, 1:32, 1:34, 1:36, 1:38 or 1:40; the second acid includes tetrafluoroboric acid, hexafluorophosphoric acid, sulfuric acid, perchloric acid, hydrofluoric acid, hydrofluoric acid, hydrobromic acid or hydrobromic acid.
[0057] In the present invention, the second acid is preferably mixed with the product obtained by the substitution reaction in the form of a second acid solution.
[0058] In the present invention, the volume ratio of the solvent to the second acid solution is 1:1-2. In a specific embodiment of the present invention, the volume ratio of the solvent to the second acid solution can be 1:1, 1:1.3, 1:1.5, 1:1.8 or 1:2; the solvent preferably includes water; the mass concentration of the second acid solution is preferably 48%.
[0059] The present invention also provides the use of the triaryl onium salt described in the above technical solution or the triaryl onium salt prepared by the preparation method described in the above technical solution in photocatalytic degradation of polyurethane materials.
[0060] In the present invention, the photocatalytic degradation of polyurethane material preferably comprises the following steps:
[0061] The triaryl onium salt, polyurethane material, alcohol compound, acidic co-catalyst and organic solvent described in the above technical solution are mixed and then photocatalytically degraded in an oxygen atmosphere.
[0062] In the present invention, the mixing preferably includes placing the triaryl onium salt and the polyurethane material in a reaction bottle, setting the atmosphere in the reaction bottle to an oxygen atmosphere, and then adding an alcohol compound, an acidic co-catalyst and an organic solvent.
[0063] In the present invention, the amount of the triaryl onium salt is preferably 0.1-1% of the amount of the polyurethane material. In a specific embodiment of the present invention, the amount of the triaryl onium salt can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1% of the mass of the polyurethane material.
[0064] In the present invention, the polyurethane material preferably has a structure shown in formula (1):
[0065]
[0066] R 1 With R 2 is an alkoxy group or an alkyl group.
[0067] In the present invention, the amount of the acidic co-catalyst is preferably 100-400% of the amount of the polyurethane material. In a specific embodiment of the present invention, the acidic co-catalyst can be 100%, 150%, 200%, 250%, 300%, 350% or 400% of the molecular weight of the polyurethane plastic model; the acid pre-catalyst preferably includes one or more of formic acid, acetic acid, phosphoric acid, perchloric acid and trifluoroacetic acid.
[0068] In the present invention, the ratio of the amount of the polyurethane material to the volume of the alcohol compound is preferably 0.1-2 mol:1L. In a specific embodiment of the present invention, the ratio of the amount of the polyurethane material to the volume of the alcohol compound can be 0.1 mol:1L, 0.5 mol:1L, 0.8 mol:1L, 1 mol:1L, 1.2 mol:1L, 1.5 mol:1L, 1.8 mol:1L or 2 mol:1L: the alcohol compound preferably includes one or more of methanol, ethanol, n-propanol and n-butanol.
[0069] In the present invention, the ratio of the amount of the polyurethane material to the volume of the organic solvent is preferably 0.1 to 2 mol:1L. In a specific embodiment of the present invention, the ratio of the amount of the polyurethane material to the volume of the organic solvent may be 0.1 mol:1L, 0.5 mol:1L, 0.8 mol:1L, 1 mol:1L, 1.2 mol:1L, 1.5 mol:1L, 1.8 mol:1L or 2 mol:1L; the organic solvent preferably includes one or more of acetonitrile, dichloromethane, chloroform, ethyl acetate, tetrahydrofuran, dimethyl sulfoxide, chlorobenzene and toluene.
[0070] In the present invention, the wavelength of the light used for the photocatalytic degradation is preferably 390 to 460 nm.
[0071] In the present invention, the temperature of the photocatalytic degradation is preferably 25-50°C, and the time is preferably 1-48h; in a specific embodiment of the present invention, the temperature of the photocatalytic degradation can be 25°C, 30°C, 35°C, 40°C, 45°C or 50°C, and the time of the photocatalytic degradation can be 1h, 6h, 12h, 18h, 24h, 30h, 36h, 42h or 48h.
[0072] The triaryl onium salt provided by the present invention and its preparation method and application are described in detail below in conjunction with the examples, but they should not be construed as limiting the scope of protection of the present invention.
[0073] Example 1
[0074] Preparation of triarylpyrylium salt PS1 photocatalyst:
[0075] 0.75 g of 4-ethoxybenzaldehyde and 1.64 g of 4-ethoxyacetophenone were dissolved in 4 mL of toluene. 1.5 mL of boron trifluoride etherate was added and the mixture was heated under reflux for 4 h. After the reaction was completed, ether was added to precipitate the product. Finally, the product was collected by filtration and purified by column chromatography to obtain 1.6 g of photocatalyst product PS1 with a yield of 62%.
[0076] Figure 2 This is the H NMR spectrum of the triarylpyrylium salt photocatalyst PS1.
[0077] Depend on Figure 2 It can be seen that the structure of photocatalyst PS1 is correct, and the number of hydrogen atoms at each position and the peak shift are correct. The nuclear magnetic resonance hydrogen spectrum data of PS1 is: 1 H NMR (400MHz, Acetonitrile-d3) δ8.43-8.01(m,8H),7.28-7.10(m,6H),4.24(qd,J=7.0,1.8Hz,6H),1.44(t,J=6.9Hz,9H).
[0078] Application Example 1
[0079] The degradation of polyurethane model molecules was catalyzed by triarylpyrylium salt PS1 photocatalyst. The reaction process is as follows:
[0080]
[0081] Add 0.05 mg of PS1 photocatalyst, 26.8 mg of polyurethane model molecule, 1 mL of acetonitrile, 1 mL of methanol, and 7 microliters of concentrated phosphoric acid (mass concentration of 85%) to a dry reaction bottle. After stirring and reacting for 12 hours under blue light irradiation, sampling and nuclear magnetic resonance detection were observed, and the degradation of the polyurethane model molecule was observed to be complete, with a degradation rate of 98%. After the reaction, the products N-para-carbamic acid ethyl ester benzaldehyde, N-para-carbamic acid ethyl benzoate, and N-para-carbamic acid ethyl ester benzyl methyl ether were obtained, with yields of 8%, 12%, and 28%, respectively.
[0082] Figure 3 This is a diagram of the clarity of the solution before and after the reaction under blue light irradiation in Application Example 1.
[0083] Depend on Figure 3 It can be seen that the polyurethane model molecules with poor solubility have been degraded into small organic molecules with better solubility after being irradiated with blue light.
[0084] The obtained product H NMR spectrum data are as follows:
[0085] N-ethylparabenzaldehyde: 1 H NMR (400MHz, Chloroform-d) δ10.25 (s, 1H), 8.21-8.14 (m, 2H), 7.95-7.84 (m, 2H), 4.60 (q, J = 7.1Hz, 2H), 1.67 (d, J = 14.3Hz, 3H).
[0086] N-(4-aminoethyl)benzoate methyl ester: 1 H NMR (400MHz, Chloroform-d) δ8.07-7.91(m,2H),7.55-7.39(m,2H),6.75(s,1H),4.25(q,J=7.1Hz,2H),3.89(s,3H),1.32(t,J=7.1Hz,3H).
[0087] N-carbamic acid ethyl benzyl ether: 1H NMR (400MHz, Chloroform-d) δ7.37(m,2H),7.27(m,J=7.9Hz,2H),6.73(s,1H),4.41(s,2H),4.22(q,J=7.1Hz,2H),3.36(s,3H),1.31(t,J=7.2Hz,3H).
[0088] Example 2
[0089] Preparation of triarylpyrylium salt PS2 photocatalyst:
[0090] 0.82 g of 4-n-propoxybenzaldehyde and 1.78 g of 4-n-propoxyacetophenone were dissolved in 4 mL of toluene. 1.5 mL of boron trifluoride ether was added and the mixture was heated under reflux for 4 h. After the reaction was completed, ether was added to precipitate the product. Finally, the product was collected by filtration and purified by column chromatography to obtain 1.3 g of photocatalyst product PS2 with a yield of 46%.
[0091] Application Example 2
[0092] The degradation of polyurethane model molecules was catalyzed by triarylpyrylium salt PS2 photocatalyst. The reaction process is as follows:
[0093]
[0094] Add 0.75 mg of PS2 photocatalyst, 268 mg of polyurethane model molecule, 1 mL of acetonitrile, 1 mL of methanol, and 0.1 mL of concentrated phosphoric acid (mass concentration of 85%) to a dry reaction bottle. Stir the reaction for 12 hours under blue light irradiation, take samples for nuclear magnetic resonance detection, and observe that the polyurethane model molecule is completely degraded with a degradation rate of 100%. After the reaction, the products N-para-carbamic acid ethyl ester benzaldehyde, N-para-carbamic acid ethyl benzoate, and N-para-carbamic acid ethyl ester benzyl methyl ether are obtained with yields of 6%, 13%, and 29%, respectively.
[0095] Example 3
[0096] Preparation of triarylpyrylium salt PS 3 photocatalyst:
[0097] 0.89 g of 4-n-butoxybenzaldehyde and 1.92 g of 4-n-butoxyacetophenone were dissolved in 4 mL of toluene. 1.5 mL of boron trifluoride etherate was added and the mixture was heated under reflux for 4 h. After the reaction was completed, ether was added to precipitate the product. Finally, the product was collected by filtration and purified by column chromatography to obtain 1.59 g of photocatalyst product PS 3, with a yield of 52%.
[0098] Application Example 3
[0099] The degradation of polyurethane model molecules was catalyzed by triarylpyrylium salt PS 3 photocatalyst. The reaction process is as follows:
[0100]
[0101] Add 12.2 mg of PS 3 photocatalyst, 2.68 g of polyurethane model molecule, 5 mL of acetonitrile, 5 mL of methanol, and 1.4 mL of concentrated phosphoric acid (mass concentration of 85%) to a dry reaction bottle. Stir the reaction for 24 hours under blue light irradiation, take samples for nuclear magnetic resonance detection, and observe that the polyurethane model molecule is completely degraded, with a degradation rate of 95%. After the reaction, the products N-para-carbamic acid ethyl ester benzaldehyde, N-para-carbamic acid ethyl benzoate, and N-para-carbamic acid ethyl ester benzyl methyl ether are obtained, with yields of 5%, 10%, and 32%, respectively.
[0102] Example 4
[0103] Preparation of triarylthiopyranium salt PS 7 photocatalyst:
[0104] 0.96g of 4-bromobenzaldehyde and 2.06g of 4-bromoacetophenone were dissolved in 4mL of toluene. 1.5mL of boron trifluoride ether was added and the reaction was refluxed for 4h. After the reaction was completed, ether was added to precipitate the product. Finally, 1.14g of tri(4-bromophenyl)pyrylium salt was obtained by filtration and purification by column chromatography, with a yield of 35%. 1.26g of the prepared tri(4-bromophenyl)pyrylium salt, 13mL of water and 0.625g of sodium sulfide were mixed and stirred at room temperature. After the reaction solution turned red, 13mL of tetrafluoroboric acid aqueous solution with a mass concentration of 48% was added to continue the reaction for 1h. After the reaction was completed, ether was added to precipitate the solid. Finally, 1.16g of the photocatalyst product PS 7 was obtained by filtration and purification by column chromatography, with a yield of 90%.
[0105] Application Example 4
[0106] The degradation of polyurethane model molecules was catalyzed by triarylthiopyranium salt PS 7 photocatalyst. The reaction process is as follows:
[0107]
[0108] Add 129 mg of PS 7 photocatalyst, 3.66 g of polyurethane model molecule, 10 mL of acetonitrile, 10 mL of methanol, and 1.4 mL of concentrated phosphoric acid (mass concentration of 85%) to a dry reaction bottle. Stir the reaction for 16 hours under blue light irradiation, take samples for nuclear magnetic resonance detection, and observe that the polyurethane model molecule is completely degraded, with a degradation rate of 100%. After the reaction, the products N-p-trimethylacetylaminobenzaldehyde, N-p-trimethylacetylaminobenzoic acid methyl ester, and N-p-trimethylacetylaminobenzyl methyl ether are obtained, with yields of 4%, 7%, and 34%, respectively.
[0109] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A triaryl onium salt, characterized in that: It has the structure shown in Formula I: X is O or S, Y is BF4, PF6, SO4, ClO4, F, Cl, Br or I, wherein R 3 ~R 6 Independently include one or more of hydrogen atoms, hydroxyl groups, nitro groups, cyano groups, isocyano groups, isocyanate groups, boronate groups, sulfone groups, halogen groups, alkyl groups, substituted alkyl groups, alkoxy groups, substituted alkoxy groups, phenoxy groups, aryl groups, substituted aryl groups, heteroaryl groups, acyl groups and ester groups.
2. The triaryl onium salt according to claim 1, characterized in that The number of carbon atoms of the alkyl, substituted alkyl, alkoxy, substituted alkoxy, acyl or ester group is independently 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15; The number of carbon atoms of the substituted aryl and heteroaryl groups is independently 6, 7, 8, 9, 10 or 11.
3. The triaryl onium salt according to claim 1 or 2, characterized in that The triaryl onium salt has a structure shown in any one of PS1 to PS 9:
4. The method for preparing the triaryl onium salt according to any one of claims 1 to 3, characterized in that: The following steps are involved: The compound represented by formula II, the compound represented by formula III, an organic solvent and a first acid are mixed and subjected to a condensation cyclization reaction to obtain a triaryl onium salt in which X is O; the first acid comprises boron trifluoride etherate, hexafluorophosphoric acid, sulfuric acid, perchloric acid, hydrofluoric acid, hydrofluoric acid, hydrobromic acid or hydrobromic acid; The molar ratio of the compound represented by the structure of formula II to the compound represented by the structure of formula III is ≤0.5; The triaryl onium salt wherein X is O, a solvent and a sulfide are mixed to carry out a substitution reaction, and then mixed with a second acid to acidify and form a salt, thereby obtaining a triaryl onium salt wherein X is S; The second acid includes tetrafluoroboric acid, hexafluorophosphoric acid, sulfuric acid, perchloric acid, hydrofluoric acid, hydrofluoric acid, hydrobromic acid or hydrobromic acid.
5. The preparation method according to claim 4, characterized in that: The molar ratio of the compound represented by the structure of formula II to the first acid is 1:2-6.
6. The preparation method according to claim 4 or 5, characterized in that: The molar ratio of the compound represented by the structure of formula II to the compound represented by the structure of formula III is 1:2 to 2.
4.
7. The preparation method according to claim 4, characterized in that: The molar ratio of the triaryl onium salt wherein X is O to the sulfide is 1:3-6.
8. The preparation method according to claim 4 or 7, characterized in that: The molar ratio of the triaryl onium salt wherein X is O to the second acid is 1:30-40.
9. Use of the triaryl onium salt according to any one of claims 1 to 3 or the triaryl onium salt prepared by the preparation method according to any one of claims 4 to 8 in photocatalytic degradation of polyurethane materials.
10. The use according to claim 9, characterized in that: The photocatalytic degradation of polyurethane material comprises the following steps: The triaryl onium salt described in any one of claims 1 to 3 or the triaryl onium salt prepared by the preparation method described in any one of claims 4 to 8, a polyurethane material, an alcohol compound, an acidic co-catalyst and an organic solvent are mixed and then photocatalytically degraded in an oxygen atmosphere.
Citation Information
Patent Citations
Method for preparing narrow-distribution polyolefin through photocatalytic ring-opening metathesis polymerization
CN114195987A
Coupling photocatalysis controllable cationic polymerization method
CN114539453A
Polyurethane degradation and recovery method and degradation product thereof
CN118420973A